x+13=24/4x+13=24

Simple and best practice solution for x+13=24/4x+13=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+13=24/4x+13=24 equation:



x+13=24/4x+13=24
We move all terms to the left:
x+13-(24/4x+13)=0
Domain of the equation: 4x+13)!=0
x∈R
We get rid of parentheses
x-24/4x-13+13=0
We multiply all the terms by the denominator
x*4x-13*4x+13*4x-24=0
Wy multiply elements
4x^2-52x+52x-24=0
We add all the numbers together, and all the variables
4x^2-24=0
a = 4; b = 0; c = -24;
Δ = b2-4ac
Δ = 02-4·4·(-24)
Δ = 384
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{384}=\sqrt{64*6}=\sqrt{64}*\sqrt{6}=8\sqrt{6}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-8\sqrt{6}}{2*4}=\frac{0-8\sqrt{6}}{8} =-\frac{8\sqrt{6}}{8} =-\sqrt{6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+8\sqrt{6}}{2*4}=\frac{0+8\sqrt{6}}{8} =\frac{8\sqrt{6}}{8} =\sqrt{6} $

You can always share this solution

See similar equations:

| .756=x/(x+10000) | | 6c+5/3=4c+1/2+5c/6 | | 1=0.25(2x+8) | | 3a+20=70 | | (4+9+16÷4)-8-3×5=z | | (4+9+16÷4)-8-3×5=s | | 55x+2=2*2-2x55 | | 3(x+1)=4(x+5) | | 6m+7=49* | | 3.8+4.5x-1.4=8.5 | | 0.25/3=x/11/3 | | -685+m/4=-11 | | 2x=40-12 | | 17x-6=7x-6 | | (X+4)+(3x-7)=(x-2)+(3x+8) | | 7x+x+8=56 | | x+2x+4x=?7x | | 7x^2+86x+399=0 | | (9?x)?(2?x)=7 | | 9?x?2?x=7 | | .3x+.5x(50-x)=18 | | 49x+2=0 | | -6x+-55=1 | | -6x+(-55)=1 | | -6x-20=70 | | 15x^2-46+16=0 | | (3a-2)(5a-4)=(3a-2) | | 2(-1)-9y=-25 | | n+5-1=-1 | | n+5?1=?1 | | 2(5c+2)-2c=3(2c=3)=7 | | 5^2x+5=12^x |

Equations solver categories